2002
DOI: 10.1017/s1355838202022070
|View full text |Cite
|
Sign up to set email alerts
|

PSF and p54nrb bind a conserved stem in U5 snRNA

Abstract: PTB-associated splicing factor (PSF) has been implicated in both early and late steps of pre-mRNA splicing, but its exact role in this process remains unclear. Here we show that PSF interacts with p54 nrb , a highly related protein first identified based on cross-reactivity to antibodies against the yeast second-step splicing factor Prp18. We performed RNA-binding experiments to determine the preferred RNA-binding sequences for PSF and p54 nrb , both individually and in combination. In all cases, iterative sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
122
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 74 publications
7
122
1
Order By: Relevance
“…1B) is consistent with cosedimentation of PSF with splicing complexes. 23 However, to our surprise, similar if not identical results were obtained when immunoprecipitation reactions were performed under splicing conditions but without the addition of AdML pre-mRNA (Fig. 1A, compare lanes 3 and 4).…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…1B) is consistent with cosedimentation of PSF with splicing complexes. 23 However, to our surprise, similar if not identical results were obtained when immunoprecipitation reactions were performed under splicing conditions but without the addition of AdML pre-mRNA (Fig. 1A, compare lanes 3 and 4).…”
Section: Resultssupporting
confidence: 72%
“…41 Previously, we showed that PSF and p54 nrb interact with U5 snRNA. 23 During further analysis of this interaction by immunoprecipitation (IP) with PSF-specific antibodies, we show here that all five U snRNPs co-IP with PSF when HeLa nuclear extracts are adjusted to splicing conditions, regardless of the addition of pre-mRNA. Sedimentation analyses confirmed the formation of large PSF-containing multi-snRNP complexes in nuclear extracts adjusted to conditions normally used for in vitro splicing.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations